Implementation of Constructive Written Feedback and Constructive Video Feedback on Writing Performance of Undergraduate Learners - Zargaran, Zahra (Journal of University Teaching and Learning Practice, 2025)
Providing constructive feedback in writing classes is academically fruitful, and integrating technology into the feedback process has added value. However, there have been few comparisons of video constructive feedback and written constructive feedback. For this purpose, a quasi-experimental study was conducted with 45 male and female intermediate students at the University of Technology and Applied Sciences (UTAS) in Shinas, Oman. The population were grouped into two experimental and one control group. Of the two experimental groups, one received constructive written feedback, while the other received constructive video feedback. The control group feedback was not either of the ones used for the experimental groups. After six treatment sessions, to measure the effect of constructive written and video feedback, a writing post-test was administered to students from all three groups, and the pre-test and post-test writing scores were compared. An independent-sample Kruskal-Wallis test was conducted to compare the groups' writing scores and to detect differences between the effects of the two feedback types., Students' improvement in post-test writing scores was evident when they used constructive video feedback. Although both experimental groups showed the benefits of using constructive feedback, integrating video into the process of giving constructive feedback resulted in a statistically more significant improvement in the post-test results of the students.